Clinical and Psychological Predictors of Acute Coronary Syndrome Symptom Severity - Ahmed, Fatma Refaat; AbuRuz, Mohannad; Al-Yateem, Nabeel; Gamil, Rawia; Mottershead, Richard; Mostafa, Heba (Jordan Medical Journal, 2025)
Introduction: Egypt is a low-income country which accounted for 16% of the MENA region’s 1.3 million CVD mortalities in 2015. Traditional Egyptian cultural, social contexts and religious beliefs are different from those in high-income Western counties where most CVD research is conducted, which may have significant impacts on patients’ psychological responses to acute illness. Therefore, this study aimed to identify the clinical and psychological predictors early during ACS course of disease. Method: In this cross-sectional study, the symptoms of 255 acute coronary syndrome patients at three university hospitals in Alexandria, Egypt, were measured using the Arabic Anxiety and Stress Subscales of Depression, Anxiety and Stress Scale (DASS-21) and Arabic Controlled Attitude Scale (CAS-R). Multiple linear regression analysis was used to identify clinical and psychological predictors of symptom severity. Results: History of diabetes, hypertension, and hyperlipidemia, perceived control, anxiety, and stress scores were independent predictors for all studied symptoms (chest pain, fatigue, and dyspnea). The models described variance of 15% for chest pain, 29% for fatigue, and 16% for dyspnea. Conclusion: This study revealed that anxiety and stress levels are predictors of increased symptoms severity, whereas history of DM, HTN, and hyperlipidemia, and perceived control level were independent predictors for all symptoms (chest pain, fatigue, and dyspnea).